Isolation of aerobic bacterial agents from the lungs of sheep and goats with pneumonia and detection of Pasteurella multocida and Mannheimia haemolytica by pollymerase chain reaction - Özbey, G; Muz, A (Tubitak Scientific & Technological Research Council Turkey, 2004)
The purpose of this study was to isolate Pasteurella spp and other aerobic bacterial agents from the lungs of sheep and goats with pneumonia and to identify Pasteurella multocida and Mannheimia haemolytica by both culture methods and polymerase chain reaction (PCR). In addition, mouse pathogenecity tests were carried out on suspected P. multocida isolates. In the examination of lung samples collected from sheep, 15 (4.3%) P. multocida and 8 (2.3%) M. haemolytica strains were isolated and identified. The numbers of species identified in the goat samples were 1 (0.7%) for P. multocida and 6 (4%) for M. haemolvtica. The differences between the numbers of P. multocida and M. haemolytica strains isolated from the sheep and goat lung samples were not statistically significant (P = 0.2 in sheep and P = 0. 12 in goats). Thirteen (86.7%) P. multocida isolates were positive in the mouse pathogenecity test in sheep. One P. multocida isolate from goats was also positive in the mouse pathogenecity test. All P. multocida and M. haemolytica strains that tested positive by culture also tested positive by PCR. However, no toxigenic P. multocida were detected in any isolates by PCR using primers derived from the toxA gene. In conclusion, this study showed the feasibilty of PCR for the accurate and rapid identification of P. multocida and M. haemolytica.
Keywords: pneumonia; sheep; goats; Pasteurella multocida; Mannheimia haemolytica; polymerase chain reaction; culture